THE MONEY DEMAND FUNCTIONS IN ISLAMIC ECONOMY: NEW EVIDENCE FROM IRAN-ARDL APPROACH - Sadeghi, Farzaneh; Khadivy Rofougar, Saeed (Journal of Islamic Monetary Economics and Finance, 2018)
The demand for money is one of the most fundamental issues of the monetary economy for policy decision. On the other hand, according to the principle of prohibition of Riba, attitudes about the money market conditions in Islamic economics, is quite different from conventional economics. Hence achieving the money demand function in an Islamic country would be necessary. Most studies about the money demand in Islamic economy used the Keynesian approach, while in modern macroeconomics, money demand function derived by using the microeconomics-based approach. Hence in this article investigate some models of the microeconomics-based approach, then, in accordance with Islamic principles, it choose the best among them that is shopping-time model. After that we derive the Islamic money demand function. The results indicate that the demand for money is the function of income and rental rates of sukuk. The marginal product of capital due to an additional unit of income spend for Infaq (spending in Allah's way), depend on the expected inflation rate, depreciation rate and rental rates of Sukuk. In this paper, apply ARDL approach to estimate the money demand function in Islamic republic of Iran in period of 1978-2008 i.e. after Islamic revolution. The results suggested that M1 and M2 money demand are co-integrated with income and rental rate of Sukuk. Incorporating CUSUM and CUSUMSQ tests into co-integration analysis, we conclude that M2 money demand is more stable than M1.